2021
DOI: 10.1002/2688-8319.12098
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing ecological integrity while preserving ecosystem services: Constructing soft‐sediment islands in a shallow lake

Abstract: Ecosystems are increasingly managed to provide multiple benefits to humans, which often degrades their ecological integrity. This strongly applies to aquatic ecosystems, in which engineering can enhance flood protection, drinking water supply, fisheries and recreation. Although these activities typically increase ecosystem functionality to humans, they often impair key aspects of biodiversity and natural functioning. Classical restoration of such degrading freshwater ecosystems can lead to societal opposition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
3
16
0
2
Order By: Relevance
“…If we also sampled Gastropoda attached on the wall, it only increases the gastropod number in the sheltered treatments, which will not affect the final conclusion. In our study, higher Gastropoda densities seemed related to macrophyte abundance, as we observed also elsewhere on Marker Wadden (van Leeuwen et al., 2021). Furthermore, we found that in the shelter + macrophytes treatment more Corophiidae were found.…”
Section: Discussionsupporting
confidence: 91%
“…If we also sampled Gastropoda attached on the wall, it only increases the gastropod number in the sheltered treatments, which will not affect the final conclusion. In our study, higher Gastropoda densities seemed related to macrophyte abundance, as we observed also elsewhere on Marker Wadden (van Leeuwen et al., 2021). Furthermore, we found that in the shelter + macrophytes treatment more Corophiidae were found.…”
Section: Discussionsupporting
confidence: 91%
“…Increasing plant diversity in highly modified aquatic systems can also trigger a bottom‐up cascade and increase benefits to humans, as shown by Van Leeuwen et al. (2021) who reports the progress of the restoration of a man‐made freshwater ecosystem in the Netherlands. Lake Markermeer was initially formed by creating an estuary for flood protection.…”
Section: Nbs For Halting Biodiversity Lossmentioning
confidence: 98%
“…Observations must also monitor the entire ecosystem, and not just the target species (such as the plant responsible for carbon storage or the predator of a specific pest). Trophic cascades up and down food chains can destabilise ecosystems, and ignoring these could have negative consequences, as shown by Lake Merkemeer in the Netherlands which was designed for flood protection but ultimately reduced lake biodiversity (Van Leeuwen et al., 2021). It is not trivial to determine the most suitable habitat and location for an NbS.…”
Section: Implementation and Managementmentioning
confidence: 99%
“…Het huidige Markermeer kent maar weinig natuurlijke landwaterovergangen -meer dan driekwart van de oevers in het Markermeer is verhard met basaltblokken. Voor een nadere beschrijving van het concept van de aanleg van Marker Wadden en de eerste resultaten wordt verwezen naar KIMA (2021) en Van Leeuwen et al (2021).…”
Section: Samenvattingunclassified
“…Op termijn kan Marker Wadden uitgroeien tot een voedselrijk moeras met een zodanige omvang dat de effecten uitstralen op een groter gedeelte van het Markermeer. In dat geval kunnen de eilanden een katalyserende functie hebben als organische koolstofbron die bodemprocessen versterkt (Van Leeuwen et al 2021, Van Riel et al 2019, Verdonschot et al 2021 Marker Wadden vormen een schakel in de verdere ontwikkeling van grootschalige, natuurlijke oevers.…”
Section: Potentie Marker Wadden Voor Vis En Vogels: Beheerunclassified